Structure Elucidation and Absolute Stereochemistry of Isomeric Monoterpene Chromane Esters - Batista, Joao M. [UNESP]; Batista, Andrea N. L. [UNESP]; Mota, Jonas S.; Cass, Quezia B.; Kato, Massuo J.; Bolzani, Vanderlan da Silva [UNESP]; Freedman, Teresa B.; Lopez, Silvia N.; Furlan, Maysa [UNESP]; Nafie, Laurence A. (Amer Chemical Soc, 2011)
Six novel monoterpene chromane esters were isolated from the aerial parts of Peperomia obtusifolia (Piperaceae) using chiral chromatography. This is the first time that chiral chromane esters of this kind, ones with a tethered chiral terpene, have been isolated in nature. Due to their structural features, it is not currently possible to assess directly their absolute stereochemistry using any of the standard classical approaches, such as X-ray crystallography, NMR, optical rotation, or electronic circular dichroism (ECD). Herein we report the absolute configuration of these molecules, involving four chiral centers, using vibrational circular dichroism (VCD) and density functional theory (DFT) (B3LYP/6-31G*) calculations. This work further reinforces the capability of VCD to determine unambiguously the absolute configuration of structurally complex molecules in solution, without crystallization or derivatization, and demonstrates the sensitivity of VCD to specify the absolute configuration for just one among a number of chiral centers. We also demonstrate the sufficiency of using the so-called inexpensive basis set 6-31G* compared to the triple-zeta basis set TZVP for absolute configuration analysis of larger molecules using VCD. Overall, this work extends our knowledge of secondary metabolites in plants and provides a straightforward way to determine the absolute configuration of complex natural products involving a chiral parent moiety combined with a chiral terpene adduct.